Breastfeeding Practice Associated with Stunting in Urban and Rural Areas, Scooping Review - Dwi Atikah Nuriyana; Anggorowati Anggorowati; Zubaidah Zubaidah (Indonesian Journal of Global Health Research, 2024)
Breastfeeding especially exclusive breastfeeding is one of the factors that can prevent the risk of stunting in children. However, breastfeeding practices are often not optimized due to various factors that become obstacles. Factors that influence can include the area of residence such as disparities that can be found in urban and rural area, access to education, access to health services, fulfillment of nutrition and regional inequality. Objective: This scoping review aims to explore breastfeeding practices on the incidence of stunting by urban and rural areas. Method: The authors have systematically analyzed studies published between 2019 and 2024 through the identification of articles in Scopus, Pubmed, and Science Direct database. The keywords used to support the articles search were “experience OR practice” AND mother AND breastfeeding AND “stunting OR malnutrition”. Results: A total of 10 articles were analyzed and several themes were obtained, namely: 1) exclusive breastfeeding with the incidence of stunting, 2) factors that influence exclusive breastfeeding, and 3) the benefits of breast milk, 4) the effect of region of residence on the incidence of stunting. Conclusions: This study concluded that breastfeeding practices can be influenced by the mother’s experience when breastfeeding, education, age of the mother when breastfeeding as well as the area of residence and the environment around the mother. So it is necessary to improve the services needed so that it can reduce the incidence of stunting.